2005
DOI: 10.1182/blood-2004-12-4792
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor promotes mast cell survival via inactivation of FOXO3a-mediated transcriptional induction and MEK-regulated phosphorylation of the proapoptotic protein Bim

Abstract: Mast cells are found in tissues throughout the body where they play important roles in the regulation of inflammatory responses. One characteristic feature of mast cells is their longevity. Although it is well established that mast cell survival is dependent on stem cell factor (SCF), it has not been described how this process is regulated. Herein, we report that SCF promotes mast cell survival through inactivation of the Forkhead transcription factor FOXO3a (forkhead box, class O3A) and down-regulation and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 64 publications
6
99
0
Order By: Relevance
“…As reported [20], mast cells from Bim À / À and Foxo3a À / À mice survived cytokine deprivation significantly better than wt cells, whereas the Bim DFoxo/DFoxo mast cells died at a normal rate (Fig 5D). Cytokine deprivation caused comparable levels of Bim protein upregulation in wt, Foxo3a À / À and Bim DFoxo/DFoxo mast cells (Fig 5E).…”
Section: Bim Dfoxo/dfoxo Cells Die Normally By Cytokine Withdrawalsupporting
confidence: 75%
“…As reported [20], mast cells from Bim À / À and Foxo3a À / À mice survived cytokine deprivation significantly better than wt cells, whereas the Bim DFoxo/DFoxo mast cells died at a normal rate (Fig 5D). Cytokine deprivation caused comparable levels of Bim protein upregulation in wt, Foxo3a À / À and Bim DFoxo/DFoxo mast cells (Fig 5E).…”
Section: Bim Dfoxo/dfoxo Cells Die Normally By Cytokine Withdrawalsupporting
confidence: 75%
“…This finding is in agreement with the results of several previous studies in which changes in the electrophoretic mobility of Bim EL were attributed to phosphorylation and dephosphorylation. Möller et al (47) showed that a stem cell factor-induced band shift of Bim EL in mouse mast cells was due to phosphorylation and indicated that the larger band represented phosphorylated Bim EL after treatment with alkaline phosphatase. Abayasiriwardana et al (48) also reported that this shift was abolished by alkaline phosphatase-mediated dephosphorylation but was restored if the phosphatase was inhibited by sodium orthovanadate in malignant mesothelioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The stem cell factor (SCF) (Kit ligand) is a well-known and essential factor for the growth, migration, activation and survival of human mast cells developed and cultured in vitro [93,123,133,134] or isolated from skin specimens [45,85]. SCF injected subcutaneously induces anaphylactic-like activation and degranulation of dermal mast cells in situ followed by inXammatory cell recruitment such as neutrophils, eosinophils and basophils [35].…”
Section: Regulation Of Mast Cell Number and Activity In The Psoriaticmentioning
confidence: 99%